OVERVIEW OF CHARACTERISTIC RESPONDENT OF THE PARTICIPATION OF PREGNANT WOMEN IN FATHER'S EFFORTS TO QUIT SMOKING FOR STUNTING PREVENTION TROUGH HEALTH BELIEF MODEL APPROACH - Marinda, Maya; Rohmah, Nur; Anggraini, Ike (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Based on the Primary Health Research on 2018, the smoking in the house rate for Samarinda is about 80.96%. This provides a health risk for other families who are in the house that exposed to cigarette smoke. Pregnant women and their fetus are no exception. They get a risk as a second hand smoker or third hand smoker. Like low birth weight, anemia, and etc. One of the health impacts for that risk is Stunting This study aims to describe characteristic of respondent of pregnant woman in father's efforts to stop smoking for stunting prevention. This research is a quantitative study using a survey method with a cross-sectional approach and involved 100 pregnant women whose husbands smoke as respondents in Samarinda This study result that the majority of respondents were under 30 years old (71.0%) and had a low educational background (78.0%). In terms of the number of pregnancies, the majority of respondents were in the category of not being their first pregnancy (65.0%) and not currently working (85.0%) The difference found in characteristic of respondent of pregnant woman. It should be influence participation of them in husband effort to quit smoking for stunting prevention.